KETERKAITAN AIR DEFENSE IDENTIFICATION ZONE (ADIZ) DENGAN KESELAMATAN PENERBANGAN (SAFETY AVIATION) DITINJAU DARI HUKUM UDARA: The Relationship Between Air Defense Identification Zone (Adiz) and Aviation Safety in Terms of Air Law - Wetik, Winna Elliane Karina; Nrangwesti, Ayu (Faculty of Law, Universitas Trisakti, 2024)
One of Indonesia's efforts to uphold its territorial sovereignty in the air space is by establishing an Air Defense Identification Zone (ADIZ). In its implementation, this enforcement turns out to be related to aviation safety. This connection raisedq the problem of how ADIZ is related to aviation safety in terms of international and national air law. The research method is normative research, with qualitative, descriptive data processing and the use of deductive methods in drawing conclusions. The discussion in this thesis is that there is a connection between ADIZ and aviation safety. First, the ADIZ concept is related to flight routes, where determining these routes is part of enforcing flight safety. Second, ADIZ is determined by taking into account country’s sovereignty in air space. Upholding sovereignty in air space means that countries must comply with aviation safety standards and recommendations set by the International Civil Aviation Organization (ICAO). Upholding sovereignty is also related to the aspect of aircraft nationality which is the main requirement in investigating aircraft accidents. Third, ADIZ can be realized because there is permission by subjacent state to enforcing aviation safety, national law is prioritized, although it must still pay attention to the provisions of international law.